Biohydrometallurgy: paving the way for a greener future of mineral processing in Indonesia - A mini review - Siti Khodijah Chaerun; Ronny Winarko; Frideni Yushandiana (Current Research on Bioscences and Biotechnology, 2023)
Biohydrometallurgy, a technology that employs microorganisms for metal extraction, has existed since the 1960s. As environmental regulations tighten and the quality and complexity of available ores for processing decline, this technology offers an alternative for mineral processing. Several countries, including South Africa, Russia, Chile, Australia, the United States, China, Burma, New Zealand, Peru, Uzbekistan, and Ghana, have used this method commercially in copper processing plants and gold and silver processing plants. In Indonesia, this method has not been developed or applied industrially. Given the challenges of limited capital and low-grade ore processing in the future, proposing biohydrometallurgical processing in Indonesia is worthwhile. Globally, biohydrometallurgy has become a significant area of research focus. In Indonesia, however, the investigation of biohydrometallurgy is primarily conducted at the Bandung Institute of Technology (ITB). This specific line of investigation was initiated in 2009, with an emphasis on extracting nickel (Ni) from laterite ores. Additional investigations have been undertaken to explore the extraction of metals including copper (Cu) and gold (Au). This review paper also summarizes ongoing laboratory-scale studies encompassing the extraction of lead (Pb), zinc (Zn), silicon (Si), magnesium (Mg), silver (Ag), rare earth elements (REEs), lithium (Li), strontium (Sr), phosphorus (P), potassium (K), calcium (Ca) and the application of phytomining technology and coal biomining. The research outcomes to date present a promising and potentially scalable perspective that could be advanced to pilot plant implementation and industrial application within Indonesia.